Polyunsaturated Fatty Acids and Their Derivatives: Therapeutic Value for Inflammatory, Functional Gastrointestinal Disorders, and Colorectal Cancer - Michalak, Arkadiusz; Mosińska, Paula; Fichna, Jakub (Frontiers in Pharmacology, 2016)
Polyunsaturated fatty acids (PUFAs) are bioactive lipids which modulate inflammation and immunity. They gained recognition in nutritional therapy and are recommended dietary supplements. There is a growing body of evidence suggesting the usefulness of PUFAs in active therapy of various gastrointestinal (GI) diseases. In this review we briefly cover the systematics of PUFAs and their metabolites, and elaborate on their possible use in inflammatory bowel disease (IBD), functional gastrointestinal disorders (FGIDs) with focus on irritable bowel syndrome (IBS), and colorectal cancer (CRC). Each section describes the latest findings from in vitro and in vivo studies, with reports of clinical interventions when available.